Continuous Glucose Monitoring Versus Capillary Point-of-Care Testing for Inpatient Glycemic Control in Type 2 Diabetes Patients Hospitalized in the General Ward and Treated With a Basal Bolus Insulin Regimen. (March 2016) - Gómez, Ana M.; Umpierrez, Guillermo E.; Muñoz, Oscar M.; Herrera, Felipe; Rubio, Claudia; Aschner, Pablo; Buendia, Richard
Background: Continuous glucose monitoring (CGM) may improve the management of patients with type 2 diabetes hospitalized in the general ward by facilitating the detection of hyper- and hypoglycemic episodes. However, the lack of data on the accuracy and safety of CGM have limited its application. Methods: A prospective pilot study was conducted including 38 patients hospitalized in the general ward with a known diagnosis of type 2 diabetes mellitus (DM) and hyperglycemic individuals without a history of DM with a blood sugar of 140-400 mg on admission treated with a basal bolus insulin regimen. Inpatient glycemic control and the incidence of hypoglycemic episodes were compared between detection by CGM of interstitial fluid for up to 6 days and point-of-care (POC) capillary blood glucose monitoring performed pre- and postprandially, before bedtime and at 3am . Results: No differences in average daily glucose levels were observed between CGM and POC (176.2 ± 33.9 vs 176.6 ± 33.7 mg/dl, P = .828). However, CGM detected a higher number of hypoglycemic episodes than POC (55 vs 12, P < .01). Glucose measurements were clinically valid, with 91.9% of patients falling within the Clarke error grid A and B zones. Conclusions: Our preliminary results indicate that the use of CGM in type 2 patients hospitalized in the general ward provides accurate estimation of blood sugar levels and is more effective than POC for the detection of hypoglycemic episodes and asymptomatic hypoglycemia.